Kualitas Air Pada Hutan Mangrove Di Dalam Kawasan Job Pertamina Medco E&P Tomori Sulawesi Di Kabupaten Banggai Sulawesi Tengah - Nur, Sri Ratnawaty; Ramadhanil, Ramadhanil; Umar, Husain (Mitra Sains, 2017)
This research was conducted in the area of ​​JOB Pertamina Medco E & P Tomori Sulawesi is located in the village Paisubuloli districts Batui South Banggai district, Central Sulawesi from January to March 2016. This study is explorative, as it aims to delve extensively on matters that affect the events leading water pollution. It is necessary for the analysis of parameters, such as temperature, turbidity, TSS, salinity, DO, BOD, DHL, metal-logan weight and identification of mangrove vegetation and wildlife. The results showed that temperature, TSS and pH on the fifth point monitoring sites are still in the specified quality standards. BOD value on the first point (3.94 mg/l) and a second point (4.581 mg /l) is below the quality standard that is 3 mg /l. Iron (Fe) on the first point (1.1362 mg/l) and the third point (1.3102 mg/l) showing values ​​above 1 mg / L. Boron (B) at a third point (2.922 mg/l), the fourth point (6.0138 mg/l), and the fifth point (5.9672 mg/l) indicates a value above the quality standard which is 1 mg/l, while for metals -Metal weight indicates the value that is still within the limits of the quality standards set out in Regulation No. 82 of 2011 on Control and Water Pollution. At the location of Research show Rhizophora spp the vegetation predominant located around the CPP and the existence of mangrove vegetation and fauna in the area of ​​field CPP showed that no different with the presence before their construction field development CPP even though possibly only on the composition of mangrove vegetation and fauna is reduced than before.